Identification of the novel HLA‐DQB1*03:03:02:04 allele in a Spanish individual. Issue 3 (29th January 2015) - Cervera, I.; Herraiz, M. A.; Vidart, J.; Ortega, S.; Martinez‐Laso, J.
<x xml:space="preserve">Abstract</x> HLA‐DQB1*03:03:02:04 and DQB1*03:03:02:02 alleles differ by a single point mutation in intron 2.